2020
DOI: 10.1101/2020.05.18.103176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcranial Focused Ultrasound Neuromodulation of Voluntary Movement-related Cortical Activity in Humans

Abstract: 1Transcranial focused ultrasound (tFUS) is an emerging non-invasive brain 2 stimulation tool for safely and reversibly modulating brain circuits. The 3 effectiveness of tFUS on human brain has been demonstrated, but how tFUS 4 influences the human voluntary motor processing in the brain remains 5 unclear. We apply low-intensity tFUS to modulate the movement-related 6 cortical potential (MRCP) originating from human subjects practicing a 7 voluntary foot tapping task. 64-channel electroencephalograph (EEG) is 8… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…We estimate the theoretical maximum focal gain G max ≈ 280 for SOAP assuming uniform laser illumination with a frequency, a fnumber, a water attenuation coefficient, and a working distance of 15 MHz, 0.52, 2.2 × 10 −3 dB/(cm × MHz 2 ) and 2 mm, respectively. This theoretical maximum focal gain is 5-and 92-fold higher than that of a conventional PZTbased transducer with f N of 1 and 4, respectively 20,21,[31][32][33] . In summary, OFUS taking advantage of a high NA close to the limit enables a lateral resolution less than 100 µm at 15 MHz and a focal theoretical maximum pressure up to 92-fold higher compared to a PZT-based transducer at the same frequency.…”
Section: Fabrication Of Soap and Optimization Of Optoacoustic Efficiencymentioning
confidence: 79%
See 1 more Smart Citation
“…We estimate the theoretical maximum focal gain G max ≈ 280 for SOAP assuming uniform laser illumination with a frequency, a fnumber, a water attenuation coefficient, and a working distance of 15 MHz, 0.52, 2.2 × 10 −3 dB/(cm × MHz 2 ) and 2 mm, respectively. This theoretical maximum focal gain is 5-and 92-fold higher than that of a conventional PZTbased transducer with f N of 1 and 4, respectively 20,21,[31][32][33] . In summary, OFUS taking advantage of a high NA close to the limit enables a lateral resolution less than 100 µm at 15 MHz and a focal theoretical maximum pressure up to 92-fold higher compared to a PZT-based transducer at the same frequency.…”
Section: Fabrication Of Soap and Optimization Of Optoacoustic Efficiencymentioning
confidence: 79%
“…g Theultrasound waveforms from 4 kinds of SOAPs with the same laser energy input. h The frequency spectra of ultrasound from 4 kinds of SOAPs of the NA in conventional PZT-based transducers 20,21,[31][32][33] . It is difficult for the single crystal piezoelectric material to reach a high NA due to the cracking in PZT-based single-element focused ultrasound transducers 34 .…”
Section: Fabrication Of Soap and Optimization Of Optoacoustic Efficiencymentioning
confidence: 99%
“…1 In animal models, TUS can induce focal motor responses; 2 alter functional magnetic resonance imaging (fMRI) blood oxygen level-dependent (BOLD) responses 3 and electroencephalography (EEG) signals; 4 and, in non-human primates, cause changes in behavioural performance on complex cognitive tasks. 5 A small number of studies in humans have reported neuromodulatory effects of TUS in primary sensory [6][7][8][9] and motor [10][11][12][13][14] cortex and the thalamus. 15,16 No study has yet determined whether TUS is able to modulate human higher cognitive processes and their neural substrates in a spatially and temporally specific manner.…”
Section: Introductionmentioning
confidence: 99%
“…tFUS has been shown to elicit action potentials in various in vivo and in vitro studies in cell culture and brain slices (Muratore et al, 2009; Tyler et al, 2008) as well as across a variety of animals including worms (Kubanek et al, 2018), rodents (Juan et al, 2014; Mehić et al, 2014; Niu et al, 2018; Tufail et al, 2010; Younan et al, 2013; Yu et al, 2016), monkeys (Deffieux et al, 2013; Folloni et al, 2019), as well as humans (Hameroff et al, 2013; Lee et al, 2015; Legon et al, 2014; Liu et al, 2021; Verhagen et al, 2019; Yu, Liu, et al, 2021; Zhang et al, 2021). Effects from stimulation have been found on various many levels recordings including in multi-unit activity (MUA) (Tufail et al, 2010), local field potential (LFP) (Yuan et al, 2015), the blood oxygen level dependent (BOLD) signal (Verhagen et al, 2019), and EEG (Lee et al, 2015; Legon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%